Streptomyces coelicolor macrodomain hydrolase SCO6735 cleaves thymidine-linked ADP-ribosylation of DNA - Hloušek-Kasun, A; Mikolčević, P; Rack, JGM; Tromans-Coia, C; Schuller, M; Jankevicius, G; Matković, M; Bertoša, B; Ahel, I; Mikoč, A (Elsevier, 2022)
ADP-ribosylation is an ancient, highly conserved, and reversible covalent modification critical for a variety of endogenous processes in both prokaryotes and eukaryotes. ADP-ribosylation targets proteins, nucleic acids, and small molecules (including antibiotics). ADP-ribosylation signalling involves enzymes that add ADP-ribose to the target molecule, the (ADP-ribosyl)transferases; and those that remove it, the (ADP-ribosyl)hydrolases. Recently, the toxin/antitoxin pair DarT/DarG composed of a DNA ADP-ribosylating toxin, DarT, and (ADP-ribosyl)hydrolase antitoxin, DarG, was described. DarT modifies thymidine in single-stranded DNA in a sequence-specific manner while DarG reverses this modification, thereby rescuing cells from DarT toxicity. We studied the DarG homologue SCO6735 which is highly conserved in all Streptomyces species and known to be associated with antibiotic production in the bacterium S. coelicolor. SCO6735 shares a high structural similarity with the bacterial DarG and human TARG1. Like DarG and TARG1, SCO6735 can also readily reverse thymidine-linked ADP-ribosylation catalysed by DarT in vitro and in cells. SCO6735 active site analysis including molecular dynamic simulations of its complex with ADP-ribosylated thymidine suggests a novel catalytic mechanism of DNA-(ADP-ribose) hydrolysis. Moreover, a comparison of SCO6735 structure with ALC1-like homologues revealed an evolutionarily conserved feature characteristic for this subclass of macrodomain hydrolases.